DENOTATIVE AND CONNOTATIVE MEANING IN THE SENTENCE OF “YOU GOT ME FEELING LIKE A PSYCHO” AS THE LINE OF RED VELVET SONG LYRIC - Kharisma Dinata Jakautama; Muhammad Rayhan Bustam (MAHADAYA: Jurnal Bahasa, Sastra, dan Budaya, 2022)
The research with the title as ‘Dennotative and Connotative Meaning in the Sentence of “You got me feeling like a psycho” as The Line of Red Velvet Song Lyric’ uses data taken from a song "Psycho" which was popularized by Red Velvet by using one of the linguistic studies, especially in the scope of semantics analyzed by the author. This case is interesting to study, especially on the meaning of the sentence "You got me feeling like a psycho". An interesting semantic study to analyze includes several understandings. Understanding the meaning which includes how the context of the sentence is then understanding the connotative and denotative meanings contained in it. Keyword: Semantics, Lyric, Linguistics, Psycho